Biogenic synthesis of selenium nanoparticles by Shewanella sp. HN-41 using a modified bioelectrochemical system - Cuong Tu Ho (Elsevier, 2021)
Background: Synthesis of selenium nanoparticles from selenite by Shewanella sp. HN-41 demonstrated that particle size depended on the reaction time and biomass of cells. The slow reaction and low biomass tended to form small particles. In this study, Shewanella sp. HN-41 was introduced into the anode of a nonexternal circuit bioelectrochemical system (nec_BES) to convert chemical energy from lactate to low electron current to the cathode, where selenite was reduced. Results: Our experiment with two systems, one bioelectrochemical system with a cathode flushed with nitrogen and the other with a no-nitrogen-flushing cathode, showed that the former could not produce Se nanoparticles after 21 d, but the latter formed them with an average size of 37.7 nm. The SEM and TEM images demonstrated that the particle size of 10 nm occupied over 10% and most of the particles were in the range of 30–60 nm. The XRD result and SAED image demonstrated no clear peaks of crystal and proved that the Se nanoparticles are amorphous. Conclusions: The clean Se nanoparticles were synthesized and completely separated from bacterial cells in the bioelectrochemical system. This study opened a new approach for the biological synthesis of metal nanoparticles. Finally, the Se products in the range of 30–60 nm can be tested for antimicrobial activities in medical applications.How to cite: Ho CT, Nguyen T-H, Lam T-T, et al. Biogenic synthesis of selenium nanoparticles by Shewanella sp. HN-41 using a modified bioelectrochemical system. Electron J Biotechnol 2021;54. https://doi.org/10.1016/j.ejbt.2021.07.004